Epidemiology of SARS-CoV-2 antibodies among firefighters/paramedics of a US fire department: a cross-sectional study. (6th August 2020) - Caban-Martinez, Alberto J; Schaefer-Solle, Natasha; Santiago, Katerina; Louzado-Feliciano, Paola; Brotons, Angel; Gonzalez, Marco; Issenberg, S. Barry; Kobetz, Erin
Abstract : Objectives: We estimate the point seroprevalence of SARS-CoV-2 antibodies in the frontline firefighter/paramedic workforce of a South Florida fire department located in the epicentre of a State outbreak. Methods: A cross-sectional study design was used to estimate the point seroprevalence of SARS-CoV-2 antibodies using a rapid immunoglobulin (Ig)M-IgG combined point-of-care lateral flow immunoassay among frontline firefighters/paramedics collected over a 2-day period, 16–17 April 2020. Fire department personnel were emailed a survey link assessing COVID-19 symptoms and work exposures the day prior to the scheduled drive-through antibody testing at a designated fire station. Off-duty and on-duty firefighter/paramedic personnel drove through the fire station/training facility in their personal vehicles or on-duty engine/rescue trucks for SARS-CoV-2 antibody testing. Results: Among the 203 firefighters/paramedics that make up the fire department workforce, 18 firefighters/paramedics (8.9%) tested positive for SARS-CoV-2 antibodies, of which 8 firefighters/paramedics (3.9%) were IgG positive only, 8 (3.9%) were IgM positive only and 2 (0.1%) were IgG/IgM positive. The positive predictive value (PPV) of the serological test is estimated to be 33.2% and the negative predictive value is 99.3%. The average number of COVID-19 case contacts (ie, within 6 feet of an infected person (laboratory-confirmed or probable COVID-19 patient) for ≥15 min) experienced by firefighters/paramedics was higher for those with positive serology compared with those with negative (13.3 cases vs 7.31 cases; p=0.022). None of the antibody positive firefighters/paramedics reported receipt of the annual influenza vaccine compared with firefighters/paramedics who tested negative for SARS-CoV-2 antibodies (0.0% vs 21.0%; p=0.027). Conclusion: Rapid SARS-CoV-2 IgM-IgG antibody testing documented early-stage and late-stage infection in a firefighter workforce providing insight to a broader medical surveillance project on return to work for firefighters/paramedics. Given the relatively low PPV of the serological test used in this study back in April 2020, caution should be used in interpreting test results.